A rare case of hairy cell leukemia variant with ATM nonsense mutation and ATM deletion, resulting in complete loss of function. (28th October 2021) - Wei, Q; Harada, S; Reddy, V
Abstract: Introduction/Objective: Hairy cell leukemia variant (HCL-v) is a rare B cell lymphoproliferative disorder. Although HCL- v shares some overlapping features with classic HCL, it lacks the characteristic immune-morphology and pathogenic BRAF V600E mutation seen in classic HCL and recognized as a distinct entity in the 2017 WHO classification. Approximately half of HCL-v harbors MAPK2 mutation and one third has TP53 mutation. Cytogenetic abnormalities include gain of chromosome 5, loss of chromosome 7q, and deletion of 17p13/TP53 and 11q/22 ATM gene Methods/Case Report: We report a case of HCL-v with total loss of ATM gene function. A 71-year-old male with splenomegaly presented with an outside diagnosis of splenic marginal zone lymphoma and underwent splenectomy. Flow cytometry on spleen demonstrated mature clonal B lymphoid cells and was positive for CD11c and CD103. However, unlike classical HCL, it was CD25 negative, which supports the diagnosis of HCL-v. Sections of spleen revealed most of the red pulp replaced by hairy cell leukemic infiltrate with minimal preservation of the normal lymphoid stroma. Peripheral blood smear showed atypical lymphocytosis with prominent nucleoli but most lacking circumferential shaggy contours, seen in classic HCL. Cytogenetic analysis identified a deletion in chromosome 11(q13q23), which deletes the ATM gene. NGS analysis demonstrated a nonsense variant in ATM (p. E888*). No significant sequence variants were identified in BRAF, MAP2K1 or TP53. This is the first case report of HCL-v with a deletion as well as a non-sense mutation in the ATM gene. ATM gene belongs to the PI3/PI4-kinase family, and is an important cell cycle checkpoint kinase that phosphorylates downstream proteins, including TP53, BRCA1 etc. Although detection of the ATM has therapeutic application for prostate cancer patient for poly [ADP]-ribose polymerase inhibitor treatment, the significance of loss of ATM function in hairy cell leukemia variant is unknown. Results (if a Case Study enter NA): N/A Conclusion: In conclusion, our case demonstrates that molecular test in hairy cell leukemia variant can be helpful for confirming the diagnosis as well as providing predictive information for potential target therapy. In our case, lack of MAP2K1 mutation precludes the patient for targeted therapy. In addition, the finding of novel mutation might help to understand the molecular pathogenesis in this rare entity.